DEVELOPMENT OF SEPARATE DOCUMENTED HACCP PROCEDURES FOR OPTIMIZING LOGISTICS PROCESSES ENSURING PRODUCT QUALITY AND CONFIRMING ITS COMPLIANCE WITH MARKET REQUIREMENTS - D. M. Sataeva; O. S. Kraynova (Современная наука и инновации, 2022)
The introduction of a food quality management system based on the HACCP principles, which is not only a mandatory requirement of the technical regulation of the Customs Union TR/CU 021/2011 "on food safety", but also a strategic decision for food industry organizations, is aimed at improving the results of their activities. At the same time, a properly designed quality management system provides the basis for planning, implementing, monitoring, and improving performance. That is why one of the mandatory requirements of the HACCP system is to document procedures and keep records of the results of monitoring control operations.